Addressing the Quiet Quitting Phenomenon through Human Resource Management Strategies: Innovative Approaches to Enhancing Employee Engagement and Retention - Jayanto, Imam; Saputri, Tiara; Gumilar, Bobi (PT. LITERASI SAINS NUSANTARA, 2025)
The phenomenon of quiet quitting has become a significant challenge in the modern workplace, where employees perform only the minimum required tasks without showing initiative or deeper engagement within the organization. This study aims to analyze innovative human resource management (HRM) strategies to address quiet quitting and enhance employee engagement and retention. The research employs a qualitative literature review and descriptive analysis, with data collected from Google Scholar and credible websites between 2018 and 2025. From an initial selection of 40 articles, 24 were chosen through a rigorous screening process based on relevance and source credibility. The findings indicate that effective strategies to mitigate quiet quitting include work flexibility, technology-based training, transformational leadership, performance-based incentives, and technology utilization in employee engagement monitoring. Case studies from various Indonesian companies, such as Gojek, Shopee, Tokopedia, Bukalapak, Unilever, and Telkom Indonesia, demonstrate that the implementation of these strategies can enhance employee motivation, job satisfaction, and loyalty. This study provides implications for organizations to adopt more innovative and employee-centered HRM policies to create a healthier and more productive work environment.